Diagnosis Kesulitan Belajar Siswa pada Materi Aritmatika Sosial Kelas VII SMPN 7 Sinjai - Sari, Fahmita; Nurfiana; Fadiyah, Faiza; Nurjannah; Heriyanti, Anggy (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Muhammadiyah Sinjai, 2023)
The purpose of this study was to determine students' learning difficulties in social arithmetic material in terms of structured knowledge. The subjects of this study were two seventh grade students with the lowest scores at SMP Negeri 7 Sinjai. This research method is a qualitative research with a case study approach. Data collection techniques used are observation, diagnostic tests, interviews, and documentation. The results of this study indicate that there are four types of learning difficulties, namely (1) students do not write down what is known and asked in the problem (2) students have difficulty identifying arithmetic operations according to what is asked; (3) reflected in the student's error in determining the formula; (4) students' difficulties in the calculation process. This shows that students cannot apply the formula correctly. Students also have no conclusions that can be drawn from the answers to the problems.